The Impact of New Infrastructure Construction Investment on High Quality Economic Development in the Yangtze River Delta Region - Wei, Yuhan; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
This article aims to explore in depth the impact mechanism of new infrastructure investment on high-quality economic development in the Yangtze River Delta region, providing useful references for policy makers. The Yangtze River Delta region has invested a large amount of funds in the field of new infrastructure, including 5G networks, data centers, intelligent transportation, new energy, and other fields. These investments not only promote the optimization and upgrading of regional industrial structure, but also lay a solid foundation for high-quality economic development. The impact of new infrastructure investment on high-quality economic development is reflected in the following aspects: promoting traditional infrastructure reform and promoting the transformation of old and new driving forces; Promote supply side structural reform and optimize resource allocation; Promote diversification of financing channels and stabilize capital structure; Generate spillover effects, increase employment opportunities, and improve people's well-being. Finally, we propose several policy recommendations.